Answer :

It is given that R be a function defined as f (x) = .

Let y be any element of Range f.


Then, there exists x ϵ R - such that y = f(x)



3xy + 4y = 4x


x(4 – 3y) = 4y


x =


Let us define g: Range f R - as g(y) =


Now, (gof)(x) = g(f(x)) =


And, (fog)(y) = f(g(y)) =


Therefore, gof = and fog = IRange f


Thus, g is the inverse of f


Therefore, The inverse of f is the map


: Range f R - , which is given by g(y) =

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

| Let * be a binaMathematics - Board Papers

Find the idMathematics - Board Papers

Let f : A Mathematics - Exemplar

Show that the binMathematics - Board Papers

Determine whetherRD Sharma - Volume 1

Fill in theMathematics - Exemplar